ANALISIS FAKTOR-FAKTOR PREFERENSI MAHASISWA MENABUNG DI PERBANKAN SYARIAH - Maulina, Marliah; Ismaulina, Ismaulina (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
The development of the Islamic economy began to attract the world's attention through the systems and principles and concepts of Islamic banking which are often referred to as the Islamic Banking System. This study aims to analyze the effect of the level of trust, knowledge, and the level of banking services on the preferences of students of the Islamic Economics and Business Faculty of IAIN Lhokseumawe on saving in Islamic banking. The research was conducted using quantitative methods. Sampling using the Slovin formula involving 67 students as respondents. The results of data processing with multiple linear regression testing concluded that the t test for the level of trust (X1) and service (X3) had no effect on students 'saving preferences, while Knowledge (X2) partially had a positive and significant effect on students' saving preferences. Furthermore, the simultaneous test for the three variables above does not have a positive and significant effect on student saving preferences, this is as seen in the F test table.